Market Reaction to The Announcement of Energy Asset Integration: An Event Study of PT Chandra Asri Pacific Tbk (TPIA) Shares - Sri Martina; Yoan Hendrawan Junpridan Saragih; Rohim Makumulloh (Program Studi Akuntansi Universitas Simalungun, 2026)
This study aims to analyze market reactions to the announcement of PT Chandra Asri Pacific Tbk.'s (TPIA) energy asset integration through the completion of the acquisition of Shell Energy and Chemicals Park in Singapore, which was integrated into Aster Chemicals and Energy. This research applies a quantitative approach using an event study method. The data consist of TPIA daily stock prices, market index data, trading volume, outstanding shares, and the official corporate announcement date. The event window covers five trading days before and five trading days after the effective event date. April 8, 2025, is used as the effective event date because it represents the first trading day after the transaction announcement and the stock exchange holiday period. Market reaction is measured using abnormal return, cumulative abnormal return, and trading volume activity. The results show a positive abnormal return of 7.90% on the effective event date and a positive cumulative abnormal return of 3.34% at the end of the event window. However, the paired sample t-test indicates no significant difference in abnormal return before and after the announcement, with a significance value of 0.763. The trading volume activity test also shows no significant difference, with a significance value of 0.449. These findings indicate that the energy asset integration announcement contains information descriptively, but it does not generate a strong and statistically consistent short-term market reaction. This study contributes to financial accounting, capital market, and sustainability accounting literature by explaining investor responses to strategic corporate actions related to business transformation and sustainability